Pragmatic economic valuation of adaptation risk and responses across scales Case study in Vietnam - Lan, Le Ngoc; Martínez Valle, Armando Isaac; Parker, Louis; Bourgoin, Clément; Than, Nguyen Thi; Guerten, Nora; Grosjean, Godefroy; Hung, Pham Anh; Lan, Vu Cong; Tran, Vuong Thuc; Ha, Pham Quang; Thong, Dao Van; et al. (2016)
Vietnam is one of the countries particularly vulnerable to climate change. Increased temperatures, increased salinity intrusion due to sea-level rise and altering precipitation patterns significantly affect livelihood options of smallholder farmers, resulting in losses in agricultural production. These impacts are projected to become increasingly severe, hence, adaptation to climate change and sensitivity needs to be assessed and adaptation measures taken. This study provides a vulnerability assessment based on the results for exposure, sensitivity and adaptive capacity. This includes present and projected future climatic conditions and hazards, crop suitability analyses and socioeconomic assessments on a district scale. In addition, a case study is presented focusing on the two provinces of Tra Vinh and Ben Tre, identified as highly vulnerable in the Mekong Delta area. The case study shows opportunities, economic trade-offs and barriers of adoption of climate-smart agriculture (CSA) practices to adapt to progressive climate change.